The Effect of Social Media Brand Engagement on Customer Brand Loyalty: A Study on Skincare Brands Customers in Indonesia - Atmaja, Dodi Ria; Sari, Riska Ware Arum (UI Scholars Hub, 2023)
Abstract Manuscript type: Research Paper Research Aims: This research aims to examine the impact of brand engagement on social media on consumer brand loyalty (BL), by investigating the moderating roles of brand co-creation, brand trust, and brand experience variables. Design/methodology/approach: The study employed a purposive sampling method, involving 230 respondents. The data was analyzed using Structural Equation Modeling (SEM). Research Findings: The results show that brand experience can moderate the impact of brand co-creation (BCC) on brand loyalty (BL). However, social media brand engagement does not always have a direct impact on brand loyalty (BL), suggesting that other factors may influence consumer attitudes in the social media brand engagement dimension. Theoretical Contribution/Originality: This research contributes to the existing knowledge gap by examining the moderating effects of brand co-creation, brand trust, and brand experience on the relationship between social media brand engagement and consumer brand loyalty. Practitioner/Policy Implication: The managerial implications of this research for business people and brand owners are to maintain positive social media brand engagement to maintain consumer loyalty and brand stability. Research limitation/Implications: Future research is expected to involve more specific respondents and employ different measurement techniques. Keywords: Brand engagement, social media, brand loyalty, brand co-creation, brand trust, brand experience.